2014
DOI: 10.1248/bpb.b14-00157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short-term Polyphenol Treatment on Endothelial Dysfunction and Thromboxane A<sub>2</sub> Levels in Streptozotocin-Induced Diabetic Mice

Abstract: Diabetes is characterized by the development of endothelial dysfunction, which affects both nitric oxide (NO)-mediated relaxation and endothelium-derived contracting factors, associated with vascular oxidative stress. There is a growing body of evidence suggesting that polyphenols have several beneficial effects, such as antioxidant and anti-inflammatory activities. This study investigated whether short-term treatment with polyphenols (chlorogenic acid (CA), morin (MO), resveratrol (RV)) can improve endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…[25][26][27] Blood glucose was measured by a glucose meter (OneTouch Ultra, LifeScan, Johnson & Johnson Company, Milpitas, CA, U.S.A.). Plasma lipid parameters and plasma insulin were measured using commercially available kits (Wako Pure Chemical Industries, Ltd., Osaka, Japan and Shibayagi, Gunma, Japan, respectively).…”
Section: Measurement Of Blood Parameters and Blood Pressurementioning
confidence: 99%
“…[25][26][27] Blood glucose was measured by a glucose meter (OneTouch Ultra, LifeScan, Johnson & Johnson Company, Milpitas, CA, U.S.A.). Plasma lipid parameters and plasma insulin were measured using commercially available kits (Wako Pure Chemical Industries, Ltd., Osaka, Japan and Shibayagi, Gunma, Japan, respectively).…”
Section: Measurement Of Blood Parameters and Blood Pressurementioning
confidence: 99%
“…8) We then studied the effects of RV using aortic ring preparations from controls. We performed 2 sequential experiments to construct the concentration-response curves (1st experiment: control, 2nd experiment: RV pretreatment).…”
Section: Body Weight and Blood Glucosementioning
confidence: 99%
“…[5][6][7] We previously reported that RV increased nitric oxide (NO) production in diabetic mice. 8) However, the underlying mechanisms are complicated and remain unclear.…”
mentioning
confidence: 99%
“…22,25,[32][33][34] Functional Studies Vascular isometric force was essentially recorded as described in our previous studies. 13,17,22,25,26,28,[32][33][34] Concentration-response curves to ATP (10 for 20 min prior to PE application. To investigate the effect of endothelium on relaxations, we analyzed concentrationresponse curves in the presence/absence of endothelium of superior mesenteric arteries from Wistar rat at 17 weeks of age.…”
Section: 18)mentioning
confidence: 99%